THE INFLUENCE OF PRICE AND QUALITY OF SERVICE ON GO-RIDE CUSTOMER SATISFACTION IN PEMATANG SIANTAR CITY - Nadia Ika Purnama; Ray Ilal Ananda (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to determine and analyze the effect of price and service quality on Go-ride customer satisfaction in Pematangsiantar city. The associative approach is an approach where to find out that there is a relationship or influence between the two variables (the independent variable and the dependent variable). The population in this study is all Go-ride service users in Pematangsiantar city whose number is unknown. The researcher determined that the sample size was 100 Go-ride users. The data collection technique used classical assumption test, multiple linear regression, t test, F test and coefficient of determination. There is a positive influence between service quality and customer satisfaction. There is a positive influence between price and service quality on customer satisfaction. Keywords: Price, Service Quality, Customer Satisfaction